Predictive power of yield curve – Evidence from India. Issue 1 (March 2022) - Krishna, Geetima Das; Nag, Biswajit
Abstract: In this paper, we explore the predictive ability of the slope of the sovereign (government) yield curve for the Indian market. Instead of simply showing the predictive power of the yield curve, an attempt has been made to compare the predictive power of the yield curve slope with an estimated composite index of lead indicators (CILI) constructed with potential high frequency lead indicators. The non-agricultural GDP (NAGDP) is used as the reference series. It is observed that the slope of the yield curve is a better predictor of the turning points of the reference series compared to the CILI constructed.